Improvement of quality of life and postural balance of institutionalized elderly people undergoing to a treadmill walking training - Rodrigues Pereira, Natalia Moya [UNESP]; Pierre Massè Araya, Marcel Jean [UNESP]; Scheicher, Marcos Eduardo [UNESP] (Elsevier, 2021)
Introduction: Institutionalized older adults have fewer opportunities to participate in daily living activities and tasks in an independent manner, with greater deleterious effects on the physiological losses inherent to aging and with increased gait and balance impairment compared to community-dwelling older adults. The use of a treadmill for rehabilitation, with or without partial weight support, has been studied in different groups, but not on institutionalized older adults. Objectives: To assess the effects of a treadmill walking program on the postural balance and quality of life of institutionalized older adults. Methods: Thirty-seven institutionalized older adults: intervention group (n = 23, 75.7 ± 7.8 years) and control group (n = 14, 78.9 ± 10.2 years). A total of 10 weeks of treadmill walking, twice a week (intervention group) vs. no training (control group). Postural balance was assessed by the Tinetti test, 6-min walk test (6MWT), and 10-m walk test and Quality of life with the WHOQOL-Bref questionnaire. Results: Significant improvement was observed in balance parameters (6MWT distance: p < 0.001; gait speed 6MWT: p < 0.001; gait speed 10MWT: p < 0.001; Tinetti scale: p = 0.001), and in the physical (p = 0.01), psychological (p = 0.002), self-assessed quality of life (p = 0.01) and overall quality of life domains (p = 0.002). Conclusions: Treadmill walking program had positive effects on the postural balance and quality of life of institutionalized older adults.
Keywords: Balance; Exercise; Institutional care; Population aging; Quality of life